Pengaruh Iklan Humor Dan Loyalitas Pelanggan Terhadap Keputusan Pembelian Pada Kartu Perdana Axis Versi Kembalian - Slamet Maryoso (Universitas Bina Sarana Informatika, 2019)
The new mass media that have emerged can have a positive effect on the business world. Entrepreneurs can more easily get their product trought the media, especially television. Product can be better known to the public if they use different ads in terms of attracting consumers’ attention, ads with an element of humor are one way that advertiserscan use to attract potential customers. Quality and service for product is one of determining factors in term of consumer loyality. By using path analysing methods research on the influence of humor advertising and customer loyalty on product purchase decision can be found. If the quality offerd is good and the service is satisfactory, consumers will purchase the product in the future.Keywords: humor ads, customers loyalty, buying decision